Human capital development for SMEs in Pakistan: is the "one-size-fits-all" policy adequate?. Issue 8 (8th August 2016) - Mubarik, Shujaat; Govindaraju, Chandran; Devadason, Evelyn S.
Abstract : Purpose: Pakistan adopted 'one-size-fits-all' policy for human capital development with the assumption that the level of human capital (HC) is equal across industry and firm size. The purpose of this study is to test this major assumption on which this policy is based, by comparing the differences in the levels of HC, overall and by dimensions of HC, by industry and firm size. Design/methodology/approach: The study is based on new dataset of a sample of 750 manufacturing SME firms in Pakistan, compiled through a survey. Applying the independent sample t-test, one way analysis of variance (ANOVA) and multivariate analysis of variance (MANOVA), the hypotheses of differences in levels of overall and dimensions of human capital were tested. Findings: The results indicate significant differences in the levels of human capital by industry and firm size. The levels of human capital were found to be higher in textiles, food, metal and leather industries, and for medium-sized firms. Practical implications: The findings provide supporting evidence on the inadequacy of the current human capital development policy in Pakistan. The study therefore recommends customized human capital development policies, accounting for differences across industry and firm size. Originality/value: By taking the data on nine major dimensions of human capital from 750 manufacturing sector SMEs, the study tests the level of overall human capital and its nine dimensions by industry and size. The study also challenges the 'one-size-fits-all' policy of the government of Pakistan for developing human capital in SMEs.